PERILAKU BULLYING ANTARA SISWA TERHADAP PEMBENTUKAN KARAKTER SISWA DI SEKOLAH DASAR - Muh. Rezky. A.H., Andi; Matwear, Safitri (Jurnal Riset Guru Indonesia, 2024)
This study aims to analyze bullying and the role of teachers in handling bullying among students to develop student character. By the purpose of the research, this study uses a qualitative descriptive research method. The object of this case research is 2 cases consisting of the victim and the perpetrator. The data collection method is carried out through interviews, observations, and in-depth documentation. Data analysis technology through the stages of data collection, data presentation, data reduction, conclusion drawing and data verification. The technique of checking the validity of the data uses extended observation, continuous observation. The results of the study are as follows: (1) The researcher analyzed bullying behavior through physical and verbal contact to understand the perpetrators and victims of bullying behavior so that they could know the role of teachers in overcoming bullying problems among students. In this case, it is very important because parents at school must provide good treatment so that the perpetrators of bullying become social children and the victims of bullying become social children. Able to interact socially well and have a strong mentality to face future treatments, shuffling memories is able to solve problems on their own. (2) The factors that cause bullying behavior are not only internal factors but also external factors that are supported by the lack of strict rules given to schools so that bullying behavior can occur repeatedly, (3) The formation of student character is carried out in schools through habituation and examples, expecting students to form a character that is not only religious and has a good character in socializing so that the PPK movement becomes a reference for schools in shaping the character of students who good.